Foreign direct investment in Brazil and home country risk - Conraria, Luís Aguiar (2006)
This study looks into the factors that explain foreign direct investment in Brazil by country of origin of investment. Based on a sample of more than 100 countries that invested and have not yet invested in Brazil, multiple estimation techniques, such as the Tobit, Heckit and Probit, are used to isolate the effect of country risk on outward foreign direct investment. In sharp contrast to the findings of previous studies on the effect of home country risk on foreign investment in the United States, the findings in this paper reveal that less risky countries invest more in Brazil. These results are controlled for size of the home country, distance, trade intensity and previous investments abroad. A simple out of sample check shows that the model correctly predicts probability of investing for a large number of countries. The existing literature does not document these results.